Drought and salinity stresses induced physio-biochemical changes in sugarcane: an overview of tolerance mechanism and mitigating approaches - Kumar, Rajeev; Sagar, Vidya; Verma, Vivek Chandra; Kumari, Mala; Gujjar, Ranjit Singh; Goswami, Sanjay K.; Kumar Jha, Sudhir; Pandey, Himanshu; Dubey, Abhishek Kumar; Srivastava, Sangeeta; Singh, S. P.; Mall, Ashutosh K.; et al. (Frontiers in Plant Science, 2023)
Sugarcane productivity is being hampered globally under changing environmental scenarios like drought and salinity. The highly complex nature of the plant responses against these stresses is determined by a variety of factors such as genotype, developmental phase of the plant, progression rate and stress, intensity, and duration. These factors influence plant responses and can determine whether mitigation approaches associated with acclimation are implemented. In this review, we attempt to summarize the effects of drought and salinity on sugarcane growth. Specifically, on the plant's responses at various levels viz., physiological, biochemical, and metabolic responses to these stresses. Furthermore, mitigation strategies for dealing with these stresses have been discussed. Despite its complex genomes, conventional breeding approaches can be utilized in conjunction with molecular breeding and omics technologies to develop drought and salinity-tolerant cultivars. The significant role of plant growth-promoting bacteria in sustaining sugarcane productivity under drought and salinity cannot be overlooked.